The impact of terrorism on stock price behavior: An event study of a sample of tourism companies listed on the Iraq Stock Exchange (Entrepreneurship Journal for Finance and Business, 2024)
This study aims to demonstrate the impact of announcing the distribution of dividends in light of information asymmetry and in light of the phenomenon of terrorism for the purpose of predicting stock prices for companies listed on the Iraqi Stock Exchange. The study was applied to a sample of various market sectors, taking into account the diversity in the sectors, which included  Mosul Dam Company that met the conditions of the study, which identified the companies that distributed dividends for two consecutive years (2014-2015), and the event study method was used with a (40) day event window with a period of (20) days before and after the event to measure the information asymmetry, as the forecasting method was adopted to identify the effects. The future of the dividend decision depends on investors' decisions in light of conditions of instability. In addition, two statistical methods were used to test the study's hypotheses, namely the regression analysis method and the scenario method. The study reached a set of conclusions, the most important of which is the possibility of achieving extraordinary returns by relying on the informational content of the dividend dividend. There is also a significant impact Statistical significance for the dividend decision due to information asymmetry. The scenario method contributes to predicting stock prices better than the traditional method. One of the most important recommendations reached by the study is the necessity of adopting scientific methods to measure the impact of market-related terrorist events on the accuracy of financial results, especially the use of mathematical models to measure the impact. Market events on stock prices. It is also preferable to adopt the scenario method in predicting stock prices and financial performance and adopt it as a model that provides multiple options for financial decisions, in addition to not being satisfied with the extraordinary return as only one tool for making investment decisions, but rather other factors such as risk must be taken into account.